Mixed convection flow of viscoelastic nanofluid past a horizontal circular cylinder with viscous dissipation - Rahimah, Mahat; Sharidan, Shafie; Abdul Rahman, Mohd Kasim; Noraihan Afiqah, Rawi (Universiti Kebangsaan Malaysia, 2018)
The purpose of this study was to examine the effect of viscous dissipation on mixed convection flow of viscoelastic nanofluid past a horizontal circular cylinder. Carboxymethyl cellulose solution (CMC) is chosen as the base fluid and copper as a nanoparticle with the Prandtl number Pr = 6.2. The transformed boundary layer equations for momentum and temperature subject to the appropriate boundary conditions are solved numerically by using Keller-box method. The influenced of the dimensionless parameters such as Eckert number, mixed convection parameter, nanoparticles volume fraction and viscoelastic parameter on the flow and heat transfer characteristics is analyzed in detail and presented graphically. The results come out with the velocity profiles are increased while the temperature profiles are decreased by increasing the values of nanoparticles volume fraction and viscoelastic parameter, respectively. The graph shows that, increasing Eckert number the skin friction is also increases. The values of skin friction are increased by increasing mixed convection parameter, but the values of Nusselt number produce an opposite behavior. The present study has many applications especially in heat exchangers technology and oceanography. Therefore, in future, it is hoping to study the viscoelastic nanofluid flow past a different geometric such as sphere and cylindrical cone.